A comparative analysis of Kenneth Frampton’s critical regionalism and William J. R. Curtis’s authentic regionalism as a means for evaluating two houses by Mexican Architect Luis Barragan - Orozco, Juan Carlos (Kansas State University, 2011)
This thesis examines the notion of regional identity and connection to place as a means for developing countries to use their cultural heritage, traditional construction methods, and everyday life patterns to create a built environment appropriate for contemporary needs. Regional identity expressed through architectural form not only establishes a connection between people and the space they inhabit but also contributes to conserving the natural environment and strengthening people’s attachment to place. To support this claim, the thesis focuses on two design thinkers who have examined placemaking from a regional perspective: Architectural theorist Kenneth Frampton and his theory of critical regionalism (Frampton 1983, 1987); and architectural theorist William J.R. Curtis and his theory of authentic regionalism (1986). Using criteria derived from Frampton’s and Curtis’s theories, this thesis analyses two Mexico City houses designed by Mexican architect Luis Barragan: his home and studio, built in 1947; and the Eduardo Prieto Lopez house, built in 1950. Using contrasting criteria from Frampton and Curtis, I examine these two houses' relative success in evoking a sense of regional identity. I argue that my analysis of the two houses, first, offers possibilities for clarifying Curtis´s and Frampton’s understandings of good regional architecture; and second, indicates how local tradition might be adequately integrated with global modernity, while at the same time providing a unique sense of place.
Keywords: Kenneth Frampton; William J. R. Curtis; Luis Barragan; Critical regionalism; Authentic regionalism; Regional identity; Architecture (0729)